The Relationship between the Reasons for Higher Education Preparation and Lifelong Learning Tendencies of Open Education High School Students and Graduates - Ay, Dilek (Bartın Üniversitesi, 2022)
This study aims to reveal the relationship between the university preparation reasons and lifelong learning tendencies of the students and graduates of Open Education High School. Open Education High Schools are one of the biggest stakeholders of lifelong learning and they affiliated to the General Directorate of Lifelong Learning. In this study, survey model of descriptive research methods has been utilized. The population of the study have formed 17 students registered in Open Education High School that are affiliated to public education centers throughout Turkey additionally, 17 students who have previously graduated from Open Education High Schools. Data of the research were obtained through the two instruments: “Lifelong Tendency Scale” developed by Yelkin Diker Coşkun (2009), the interview form prepared by the researcher. The results of the study revealed that the predominant reason for attending at the Open Education High School is to pursue both education and work, which is attributed to demanding aspect of future career and preparatory criterion for the work life. Further suggestions in relation to help open high school students and graduates develop their ability to direct their lives in line with their career plans will be discussed.

Bu çalışmada hayat boyu öğrenmenin en büyük paydaşlarından biri olan Hayat Boyu Öğrenme Genel Müdürlüğü'ne bağlı bulunan Açık Öğretim Lisesi öğrenci ve mezunlarının, üniversiteye hazırlık nedenleri ve yaşam boyu öğrenme eğilimleri arasındaki ilişkinin ortaya konması amaçlanmıştır. Araştırma tarama modelinde betimsel bir çalışma niteliğindedir. Araştırmanın çalışma grubunu Türkiye genelinde halk eğitim merkezlerine kayıtlı olan açık 17 öğretim lisesi öğrencisi ve 18 açık öğretim lisesi mezunları oluşturmaktadır. Araştırmanın verileri araştırmacı tarafından hazırlanan görüşme formu ve Yelkin Diker Coşkun (2009) tarafından geliştirilen “Yaşam Boyu Öğrenme Eğilimleri Ölçeği”nden elde edilmiştir. Çalışmanın temel bulguları arasında katılımcıların hem eğitim hem de çalışma imkanınına devam edebilmek olduğu gözlemlenmektedir. Bu durum yaşam boyu öğrenme ile birlikte artan kariyer beklentisi ve iş hayatına hazırlık yapma durumuna bağlantılandırılabilir.
Açık Öğretim Lisesi Öğrenci ve Mezunlarının Yükseköğrenime Hazırlık Amaçları ve Yaşam Boyu Öğrenme Eğilimleri Arasındaki İlişki
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar